EFFECT OF PROFITABILITY, LEVERAGE AND FIRM SIZE TO CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Yanti, Ni Kadek Ayu Giri; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of profitability, leverage, and the size of the company in CSR. The theory used in this research is the signaling theory, stakeholder theory and agency theory. Samples are 35 mining companies in the Indonesia Stock Exchange (BEI) 2012-2014 by purposive sampling method. The analysis technique used is the Multiple Linear Regression Analysis. The results showed that (1) the profitability of a positive effect on CSR which indicates that the greater proftabilitas company then the company is obliged to disclose CSR, (2) leverage positive effect on the disclosure of CSR indicating that that the higher the leverage ratio of a company then CSR will the higher, (3) the size of the company's positive influence on CSR which shows that the bigger the company, the CSR policy will be more widespread.
Keywords: CSR, Profitability, Leverage, Firm Size